2021
DOI: 10.31557/apjcp.2021.22.3.671
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket, Catastrophic Health Expenditure and Distress Financing on Non-Communicable Diseases in India: A Systematic Review with Meta-Analysis

Abstract: the insurance coverage is limited and health expenditures are not covered for approximately 80% of the population (Government of India, NSSO, 2020). Therefore, the treatment cost often results in financial catastrophe and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Breaking the BBN session into multiple smaller sessions may be particularly appropriate for such patients. For an average Indian family, finances may be the primary determinant of treatment, as studies have revealed extremely high out-of-pocket and catastrophic expenditures for cancer care in India [ 30 , 31 ]. Hence, when the family insists, the oncologist has to speak about some aspects of treatment like finances, without including the patient in the conversation, which might have also contributed to the shorter session times.…”
Section: Discussionmentioning
confidence: 99%
“…Breaking the BBN session into multiple smaller sessions may be particularly appropriate for such patients. For an average Indian family, finances may be the primary determinant of treatment, as studies have revealed extremely high out-of-pocket and catastrophic expenditures for cancer care in India [ 30 , 31 ]. Hence, when the family insists, the oncologist has to speak about some aspects of treatment like finances, without including the patient in the conversation, which might have also contributed to the shorter session times.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to estimate the economic burden of cancer in the past (11)(12)(13)(14)(15)(16)(17)(18)(19). However, there were certain methodological limitations in published studies.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature to date linking COVID-19 and financial services has focused on how the pandemic has challenged the financial security of financial sector institutions (e.g., [12][13][14]), of businesses [15][16][17], and of households [18][19][20]. Similarly, the public health literature beyond COVID-19 has focused on how health problems can cause financial risk, including socalled distress financing, the phenomenon of lower-income households coping with health crises and health-related negative income shocks by relying on selling assets and over-indebtedness, in turn begetting further financial risk for the households [21][22][23]. Distress financing tends to be higher where insurance is thin and national systems lack universal healthcare.…”
Section: Introductionmentioning
confidence: 99%